Осетр русский северо-западной части Черного моря и р. Кубань - Мовчан, Ю.В. (Вестник зоологии, 1967)
301 individuals of sturgeon from the Danube, Dnieper and Kuban were studied morphometrically according to 42 characters. They were compared between themselves and with sturgeons from the Rion, Don, Kura and Volga. It was found out that on the one hand the Danube and Dnieper sturgeons are closer morphologically and on the other hand — the Kuban and Don ones. It was also established that the Black Sea populations of Acipenser giildenstiidti Bradt actually differ from the Azov and Caspian ones. On the basis of this comparison three main nations of the Black Sea-Azov sturgeon are distinguished within the limits of the Azov-Black Sea basin: Rion — Acipenser galdenstadti colchicus natio colcica natio nova, Azov — A. guldensteidti colchicus natio tanaica natio nova, incorporating the Don and Kuban schools and the Danube — A. guldenstadti colchicus natio danbuica natio nova with the Danube and Dnieper schools.